The Evolution of Ethiopian Absolutism. The Genesis and the Making of the Fiscal Military State, 1696-1913 - Tegenu, Tsegaye (Aethiopica, 1998)
Dissertation Abstract ATTENTION: Due to copy-right no online publication is provided